2010
DOI: 10.1038/cr.2010.123
|View full text |Cite
|
Sign up to set email alerts
|

Physiological levels of ATP negatively regulate proteasome function

Abstract: Intracellular protein degradation by the ubiquitin-proteasome system is ATP-dependent and the optimal ATP concentration to activate proteasome function in vitro is ~100 μM. Intracellular ATP levels are generally in the low millimolar range but ATP at a level within this range was shown to inhibit proteasome peptidase activities in vitro. Here we report new evidence that supports a hypothesis that intracellular ATP at the physiological levels bidirectionally regulates 26S proteasome proteolytic function in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 39 publications
9
108
0
Order By: Relevance
“…Table II shows the three-state parameterization of kinesin from Clancy et al [16]. Typical physiological ATP concentrations in the low millimolars [48] motivate the approximation [ATP]∼1mM, giving k + 12 , and hence ω 12 ≃ 4. The second and third transitions are considered 'irreversible,' so we assume that the remaining dissipation budget (from the 20 k B T free energy provided by ATP hydrolysis) is evenly split to these two transitions, so that ω 23 = ω 31 = 8, providing values for k − 23 and k − 31 .…”
Section: Appendix B: Additional Model Detailsmentioning
confidence: 99%
“…Table II shows the three-state parameterization of kinesin from Clancy et al [16]. Typical physiological ATP concentrations in the low millimolars [48] motivate the approximation [ATP]∼1mM, giving k + 12 , and hence ω 12 ≃ 4. The second and third transitions are considered 'irreversible,' so we assume that the remaining dissipation budget (from the 20 k B T free energy provided by ATP hydrolysis) is evenly split to these two transitions, so that ω 23 = ω 31 = 8, providing values for k − 23 and k − 31 .…”
Section: Appendix B: Additional Model Detailsmentioning
confidence: 99%
“…Of the top 10 compounds, only compound 1 was more than 10-fold less potent in blocking ODD-Luc degradation compared with Ub G76V -GFP degradation. As a further test of the selectivity of this compound we evaluated its ability to inhibit AAA ATPase activity of purified N-ethylmaleimidesensitive factor (NSF) (25) and the ATP-dependent chymotryptic activity of 26S proteasome (26). Compound 1 [which we have renamed as N 2 ,N 4 -dibenzylquinazoline-2,4-diamine (DBeQ)] was at least 50-fold less potent toward these enzymes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An intriguing hypothesis posits that physiological ATP levels may negatively regulate proteasome function under normal circumstances. 70 Powell et al 62 reported that the optimal ATP concentration for in vitro proteasome activity is <100 μmol/L and that higher ATP concentrations inhibit proteasome peptidase activities. On the other hand, it is well known that the physiological intracellular ATP concentration in many cell types is greatly higher (by a factor >10) than such values.…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 99%